Genome-guided prediction of acid resistance mechanisms in acidophilic methanotrophs of phylogenetically deep-rooted Verrucomicrobia isolated from geothermal environments - Neira, Gonzalo; Vergara, Eva; Holmes, David S. (Frontiers in Microbiology, 2022)
Verrucomicrobia is a phylum of Gram-negative bacteria that has been proposed to be deep rooted in the Tree of Life. Some are methanotrophs, oxidizing the potent greenhouse gas methane potentially ameliorating climate change. They are widespread in various environments including soil and fresh or marine waters. Recently, a clade of extremely acidophilic Verrucomicrobia, flourishing at pH < 3, were described from high-temperature geothermal ecosystems. This novel group could be of interest for studies about the emergence of life on Earth and to astrobiologists as homologs for possible extraterrestrial life. In this paper, we describe predicted mechanisms for survival of this clade at ultra-low pH and suggest its possible evolutionary trajectory from an inferred neutrophilic ancestor. Extreme acidophiles are defined as organisms that thrive in ultra-low pH environments (≤pH 3). They are important to study both for providing fundamental insights into biological mechanisms of survival and evolution but also for understanding their roles in biotechnological applications such as industrial mineral recovery (bioleaching) and mitigation of acid-mine drainage. They are also potentially a rich source of novel genes and pathways for genetic engineering of microbial strains. Acidophiles of the Verrucomicrobia phylum are unique as they are the only known aerobic methanotrophs that can grow optimally under acidic (pH 2-3) and moderately thermophilic condition (50-600C). Three moderately thermophilic genera, namely Methylacidiphilum, Methylacidimicrobium and Ca. Methylacidithermus have been described from geothermal environments. Most of the investigations of these organisms have focused on their methane oxidizing capabilities (methanotrophy) and use of lanthanides as a protein cofactor, with no extensive study that sheds light on the mechanisms that they use to flourish at extremely low pH. In this paper, we extend the phylogenetic description of this group, using whole genome information, and we identify several mechanisms, potentially involved in acid resistance, including first and second lines of defense. Phylogenetic analyses suggest that many predicted acid resistance mechanisms are evolutionarily conserved and most likely entered the acidophilic lineage of Verrucomicrobia by vertical descent from a neutrophilic common ancestor. However, it is likely that some defense mechanisms entered the acidophilic Verrucomicrobia lineage by horizontal gene transfer.